Development and Use of Large-Scale Land Information System (LIS) by Using Geographic Information System (GIS) and Field Surveying - Th. Ibraheem, Asma; M. Daham, Afrah (Iraqi Journal of Civil Engineering, 2012)
Cadastral maps are an important component of land administration in most countries. In virtually all developed countries, the needs of computerized land and geographic information systems (LIS/GIS) has given urgent impetus to computerizing cadastral maps and creating digital cadastral data bases (DCDB). This process is creating many institutional, legal, technical and administrative problems. This desire to establish DCDBs is being given increased impetus due to a new range of enabling technologies such as satellite position fixing (GPS), improved spatial data collection techniques such as digital theodolites and "soft copy" photogrammetry, as well as a vast range of new information and communications technological tools, thus contributing to the advancement and keep up with the great countries. This paper presents the problem of cadastral maps. The hitherto existing cadastre, consisting of paper maps and land registers, is now becoming insufficient. Its shortcomings force developments leading to its improvement. One of the ways is the creation of a Land Information System. A digital cadastral map is the main component of this system. The structure and information content of the map is presented, its differences from analogue maps are shown, and the process of map creation is described. A digital cadastral map can be the basis for additional thematic layers, successively converting it into a complex system for management of administrative units.